Cor, capacidade de retenção de água e maciez da carne de cordeiro maturada e injetada com cloreto de cálcio - Zeola, N. M. B. L.; Souza, P. A.; Souza, H. B. A.; Silva Sobrinho, A. G.; Barbosa, J. C. (FapUNIFESP (SciELO), 2007)
Biceps femoris, Longissimus and Triceps brachii muscles from Morada Nova lambs were submitted to ageing and calcium chloride injection. Colour, water holding capacity and tenderness were studied. Lambs were slaughtered weighting 25kg.. The muscles presented differences in colour (lightness-L*, redness-a* and yellowness- b*) 24 hours after rigor mortis instalation. Ageing intensified redness of the meats. Calcium chloride did not modify the colour of Longissimus and Triceps brachii, however, Biceps femoris became more redness after receiving calcium chloride. In relation to water holding capacity, ageing affected meats from Triceps brachii. However, it did not affect Biceps femoris and Longissimus. The calcium chloride didn't modify the water holding capacity of the muscles. Ageing influenced tenderness of Biceps femoris and Longissimus.
Colour, water holding capacity and tenderness of lamb aged and injected with calcium chloride
Keywords: Ageing; Calcium chloride; Colour; Lamb; Tenderness; Water holding capacity; Ovis aries